Specific Functions of Melanocortin 3 Receptor (MC3R) - Tulin Yanik; Seyda Tugce Durhan (Galenos Yayincilik, 2023)
Melanocortin 3 receptor (MC3R) is a G-protein coupled receptor which has been defined mostly as a regulator of the appetite/hunger balance mechanisms to date. In addition to its function regarding the weight gain and appetite control mechanisms of MC3R, recent studies have shown that MC3R controls growth, puberty, and circadian rhythms as well. Despite the drastic effects of MC3R deficiency in humans and other mammals, its cellular mechanisms are still under investigation. In this review paper, we aimed to point out the importance of MC3R regulations in three main areas: 1) its impact on weight and appetite control, 2) its role in the control of growth, puberty, and the circadian rhythm, and, 3) its protein-protein interactions and cellular mechanisms.